2017
DOI: 10.1038/s41598-017-16585-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature fabrication of an HfO2 passivation layer for amorphous indium–gallium–zinc oxide thin film transistors using a solution process

Abstract: We report low-temperature solution processing of hafnium oxide (HfO2) passivation layers for amorphous indium–gallium–zinc oxide (a-IGZO) thin-film transistors (TFTs). At 150 °C, the hafnium chloride (HfCl4) precursor readily hydrolyzed in deionized (DI) water and transformed into an HfO2 film. The fabricated HfO2 passivation layer prevented any interaction between the back surface of an a-IGZO TFT and ambient gas. Moreover, diffused Hf4+ in the back-channel layer of the a-IGZO TFT reduced the oxygen vacancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…All parameters mentioned above, except / , are affected by the charge carrier concentration of the channel layer, while / is affected by the total trap density consisting of the bulk trap density and interface trap density [19]. Therefore, the positive shift of Vth and the reduction of SS and Ioff are all benefits from the reduction of oxygen vacancies (VO) and electron concentration in the ITZO channel [17,18,20]. It is well known that VO (as donor-like states) is related to the electrons generated in the ITZO channel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All parameters mentioned above, except / , are affected by the charge carrier concentration of the channel layer, while / is affected by the total trap density consisting of the bulk trap density and interface trap density [19]. Therefore, the positive shift of Vth and the reduction of SS and Ioff are all benefits from the reduction of oxygen vacancies (VO) and electron concentration in the ITZO channel [17,18,20]. It is well known that VO (as donor-like states) is related to the electrons generated in the ITZO channel.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that Al 3+ as an oxygen binder can effectively reduce VO in AOS film [17,18]. This could be due to the lower standard electrode potential (SEP) (−1.66 V) of Al than that of In (−0.342 V), Zn (−0.761 V), and Sn (−0.13 V), which could combine easily with the oxygen vacancies (VO) [17,19,20]. This results in a reduction of oxygen vacancy and a decrease of electron concentration in the ITZO channel, and the Vth of the device is positively shifted accordingly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These oxygen vacancies serve as active trap sites and cause various reliability problems [ 15 , 16 , 17 ]. Although several countermeasures for this problem have been developed using passivation layers such as SiO 2 and HfO 2 [ 18 , 19 ], the detailed mechanisms of device degradation and recovery related with the oxygen vacancies have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%